2015
DOI: 10.3988/jcn.2015.11.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Extracorporeal Membrane Oxygenation

Abstract: Background and PurposeThe rate and outcomes of neurologic complications of patients receiving extracorporeal membrane oxygenation (ECMO) are poorly understood. The purpose of this study was to identify these parameters in ECMO patients.MethodsAll patients receiving ECMO were selected from the Nationwide Inpatient Sample between 2001-2011. The rate and outcomes of neurologic complications [acute ischemic stroke, intracranial hemorrhage (ICH), and seizures] among these patients was determined. Discharge status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 22 publications
8
118
0
3
Order By: Relevance
“…The authors of the largest study that included 23,951 patients given ECMO support reported 10.9% neurological complications [13]. Ischemic stroke, cerebral bleeding and seizure frequencies were 4.1%, 3.6% and 4.1%, respectively, but, as underlined by the authors themselves, they mixed adults, children and newborns, and were unable to distinguish patients receiving VV-and/or VA-ECMO [13]. The cerebral bleeding frequency for VV-ECMO patients observed in the systematic review (see online supplement) was 5%, similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the largest study that included 23,951 patients given ECMO support reported 10.9% neurological complications [13]. Ischemic stroke, cerebral bleeding and seizure frequencies were 4.1%, 3.6% and 4.1%, respectively, but, as underlined by the authors themselves, they mixed adults, children and newborns, and were unable to distinguish patients receiving VV-and/or VA-ECMO [13]. The cerebral bleeding frequency for VV-ECMO patients observed in the systematic review (see online supplement) was 5%, similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the ELSO registry for adult patients on VA ECMO, by the same group, found similar findings in the venoarterial cohort [9]. A decade's review of the Nationwide Inpatient Sample, that included over 23,000 patients, found that adult patients with acute ischemic stroke and intracranial hemorrhage on ECMO had higher rates of discharge to a long term facility and longer length of stay when compared to patients without neurologic injury [10].…”
Section: Epidemiologymentioning
confidence: 80%
“…Other risks associated with VA ECMO vary among patient populations, indications, and cannulation technique. Complications include hemorrhage in 30%‐70% of patients, stroke in 4%‐12% , limb ischemia in 12%‐22%, and left ventricular distention, which both delays separation from ECMO and increases areas of stasis and hematologic complications 1‐7 . Assessing the true risk of complications associated with ECMO is difficult because of the differences in populations, indications (including cardiac arrest, low cardiac output, and respiratory failure), cannulation techniques, circuitry, and anticoagulation strategies.…”
Section: Contemporary Ecmo Uses and Circuit Designsmentioning
confidence: 99%